Procedimento monitório - Oliveira, Cybele (2006)
This work aims at investigating the regular procedure of tutelage in the juridical order of Brazil, which was introduced as a form of differentiated juridical tutelage by the Law 9079, from July 14, 1995. A wide bibiographycal research was made with the objective of analysing the former historical records of the juridical tutelage, which is the subject of this analysis, as well as the changes it suffered with the years, besides some successful foreign experiences concerning this issue, especially the ones in Italy and germany. As for the defined profile by the national legislator to this procedure of contentious jurisdiction, its main polemic aspects were also analysed, not only in relation to the juridical nature of some juridical procedures likely to be released during the development of this procedure form, but also other topics which have brought in a lot of discussion, especially those related to the suitability of this tutelage when faced, for instance, to the Public Administration. The new regulation given to the fullfilment of the sentences introduced in the juridical order by the Law 11232, from December 22, 2005, has affected tremendously the procedure here analysed. Therefore it was also object of analysis, although in a brief way, once it was not relevant to the frame which guided the accomplishment of this work